2020
DOI: 10.1108/jeim-02-2020-0060
|View full text |Cite
|
Sign up to set email alerts
|

External diffusion of B2B e-procurement and firm financial performance: role of information transparency and supply chain coordination

Abstract: PurposeThe purpose of this paper is to understand the process through which external diffusion of business-to-business (B2B) e-procurement impacts firm performance. The research model has been developed to empirically examine the role of information transparency and supply chain coordination in improving the firm financial performance by external diffusion of e-procurement.Design/methodology/approachThe survey is conducted in India with a target population of purchasing professionals working on the B2B e-procu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 84 publications
2
30
0
Order By: Relevance
“…The research suggested that information transparency positively moderates the relationship between contractual control and goodwill trust. This finding is consistent with the viewpoints of Kumar and Ganguly (2020), who found that timely information disclosure is conducive to coordinating relationships. This means that information transparency is a crucial step for deeper cooperation between partners.…”
Section: Moderating Effect Of Information Transparencysupporting
confidence: 91%
“…The research suggested that information transparency positively moderates the relationship between contractual control and goodwill trust. This finding is consistent with the viewpoints of Kumar and Ganguly (2020), who found that timely information disclosure is conducive to coordinating relationships. This means that information transparency is a crucial step for deeper cooperation between partners.…”
Section: Moderating Effect Of Information Transparencysupporting
confidence: 91%
“…In a benchmarking report “Connecting the dots: navigating procurement automation” (ProcureCon, 2019) which was prepared based on survey results of 100 chief procurement officers, user experience and ease of adoption by users was among the key selection criteria for choosing the procurement automation system. This is in resonance with an academic finding that the adoption of an IT system by users is required for utilization of the full potential of the proposed system (Kumar and Ganguly, 2020b; Brandon-Jones and Kauppi, 2018). Therefore, users are required to be facilitated by providing adequate resources, TR and guidance for the successful implementation of IT projects (Ali et al , 2016; Laumer et al , 2016).…”
Section: Introductionsupporting
confidence: 58%
“…As a result, these firms can respond to dynamic market change faster than before because of IT-enabled inter-organizational systems (Lee et al, 2014;Zhao and Xia, 2014) [1]. In such a business scenario, B2B digital processes enable supply chains agility and therefore firms can respond to demands promptly (Kumar and Ganguly, 2021;Sarkis et al, 2021;Sundram et al, 2018).…”
Section: Introductionmentioning
confidence: 99%